Kurikulum Merdeka dan Pembelajaran Inklusif: Upaya Mengintegrasikan Nilai Pancasila dalam Pendidikan Dasar - Setyawan, Agung (Universitas Islam Nahdlatul Ulama Jepara, 2024)
This research aims to examine the implementation of the Merdeka Curriculum in supporting inclusive learning and integrating Pancasila values in primary education. The research method used is a qualitative approach with a case study in several elementary schools in the Bangkalan, Sampang, Pamekasan, and Sumenep regions. Data collection was carried out through observation, in-depth interviews with teachers and students, and analysis of curriculum and learning documents. The results of the study show that the Merdeka Curriculum provides flexibility for teachers in designing and implementing inclusive learning. Pancasila values such as mutual cooperation, social justice, and appreciation for diversity have been successfully integrated into learning activities. Teachers and students demonstrate a deeper understanding of these values and are able to apply them in everyday school life. The conclusion of this research is that the Merdeka Curriculum is effective in supporting inclusive learning and integrating Pancasila values in primary education. This has a positive impact on the development of students' character and creates a more inclusive and harmonious learning environment.